A detailed MSn study for the molecular identification of a dimer formed from oxidation of pinene. (April 2016) - Beck, Martin; Hoffmann, Thorsten
Abstract: Dimeric products formed in the oxidation of α- and β-pinene have been frequently observed in laboratory and field studies of biogenic SOA formation. While their existence is undoubted, their exact chemical structures remain unclear. This study uses a combined two step approach aiming on the molecular identification of the most important of the various dimers that have been observed in biogenic secondary organic aerosol formation, a dimer with the molecular weight 358 g mol −1 . The first step is the application of a functional group derivatization technique (esterification) to quantify the number of carboxylic acid groups in the target molecule. Based on the detailed interpretation of the MS n spectra (up to n = 7) of the derivatized product further information about the exact structure of the compound of interest is compiled. To increase the intensity of precursor ions for the MS n -studies and especially to facilitate successive fragmentation of the target molecule, which yields structurally informative product spectra, cationization reagents (Li +, NH 4 + ) are introduced. The results clearly point to the formation of a dimer containing three carboxylic acid groups and a structure containing a terpenylic acid building block and a pinic acid building block, strongly supporting a structure suggestion by Claeys and coworkers (Yasmeen et al., 2010). Graphical abstract: Highlights: A two step approach is used for the molecular identification of biogenic SOA dimers. A functional group derivatization method is applied to quantify carboxylic acid groups. Cationization reagents enable multiple fragmentation of the target molecule. MS n (n = 7) spectra of the derivatized product have been recorded and interpreted. The target dimer likely contains a terpenylic acid and a pinic acid building block.